Is Mar del Plata (Argentina) a sustainable city? An evaluation of the sustainability of urban and peri-urban areas using indicators - Zulaica, Maria Laura (2019)
The urbanization process in Latin America has reached unprecedented levels. The need to mitigate its effects and improve cities sustainability has become a pressing challenge. In this context, the assessment of sustainability acquires an increased recognition as a diagnosis tool to advance towards the ecological, social, economic and political objectives of sustainable development. On the basis of previous studies, this paper is intended to comparatively evaluate the urban and environmental sustainability of Mar del Plata city (Argentina) and its peri-urban area. A Sustainability Index (SI) was built. The most favourable SI values were generally found in the urban area, while the most critical ones were identified in the peri-urban area. The incidence of the topics in the SI, reveals differences between the urban and peri-urban areas. The outcome is expected to strengthen policy integration for present and future generations leading to the Sustainable Development Goals at a local scale.